UJI PENERIMAAN KONSUMEN KOPI ARABIKA ARGOPURO DENGAN PENGOLAHAN NATURAL, HONEY DAN FULLWASH - Mahardika, Nidya Shara; Suwasono, Sony; Plus, Melinda Lady; Amilia, Winda (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
Argopuro Arabica coffee is coffee grown in Klungkung Village, Sukorambi District, Jember Regency by the Santoso Farmer Group. Klungkung Arabica coffee needs to be tested together with specialty coffee to determine consumer acceptance in order to realize the desire of Klungkung Village farmer groups to market their products throughout Indonesia and even abroad. The purpose of this study is to determine the segmentation and positioning of Arabica coffee "Klungkung Coffee" with natural, honey, and fullwash processing. The data collection method used a questionnaire for organoleptic tests and coffee brightness tests. Data analysis using One Way Anova and MDS (Multi Dimensional Scaling). The research was conducted at the Macro Caffe Roastery from December 2020 to January 2021. It can be concluded that the segmentation of coffee products is targeted at male consumers, aged 20-29 years, educated students / college students with a high school education. Product positioning results that Argopuro Klungkung Arabica coffee that is ready to be developed is Klungkung Coffee with Fullwash and Honey processing. This can be seen on the proximity map which shows that Klungkung Fullwash and Honey coffees are close to specialty coffees (Aceh Gayo, Ijen Fullwash, and Bali Kintamani). This proximity means that Klungkung Coffee can compete with specialty coffee.